TEACHING AT THE RIGHT LEVEL PADA PJOK: APAKAH PENDEKATAN TERSEBUT DAPAT MENINGKATKAN PEMAHAMAN SISWA KELAS V? - Wardaniyatul Hikmah; Faridha Nurhayati; Yoga Rikhi; Zegi Indirwan; Yunita Herlina; Zyan Farodies; Zukhrufi Saptatoriq; M.Rofi'i Zakaria (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research discusses the application of the Teaching at the Right Level (TaRL) approach, which is a learning method that adapts teaching materials to the level of understanding of students, not based on age or grade. The purpose of this study was to determine whether there was an increase in the understanding of grade V students by applying Teaching at the Right Level (TaRL) learning. The research method used was Classroom Action Research (PTK) with a quantitative descriptive approach, carried out in two cycles. The research subjects consisted of 14 grade V students, consisting of 12 female students and 2 male students. Data collection techniques used tests, with instruments in the form of evaluation sheets given at the end of learning. The results showed that in cycle I, the average student score was 75.71 with an individual completeness rate of 57.14% (category “Not Good”). In cycle II, the average score increased to 87.14 with a learning completeness of 85.71% (category “Good”). These results show that there is a significant increase in the understanding of grade V students by applying the Teaching at the Right Level (TaRL) approach to the learning process. Keywords: Teaching at the Right Level, Physical Education, Sports and Healt, The Dangers of Smoking, Elementary School